Methods of trichlorosilane synthesis for polycrystalline silicon production. Part 1: Direct synthesis - Vladimir N. Jarkin (Pensoft Publishers, 2021)
Novel technical solutions and ideas for increasing the yield of solar and semiconductor grade polycrystalline silicon processes have been analyzed. The predominant polycrystalline silicon technology is currently still the Siemens process including the conversion of technical grade silicon (synthesized by carbon-thermal reduction of quartzites) to trichlorosilane followed by rectification and hydrogen reduction. The cost of product silicon can be cut down by reducing the trichlorosilane synthesis costs through process and equipment improvement. Advantages, drawbacks and production cost reduction methods have been considered with respect to four common trichlorosilane synthesis processes: hydrogen chloride exposure of technical grade silicon (direct chlorination, DC), homogeneous hydration of tetrachlorosilane (conversion), tetrachlorosilane and hydrogen exposure of silicon (hydro chlorination silicon, HC), and catalyzed tetrachlorosilane and dichlorosilane reaction (redistribution of anti-disproportioning reaction). These processes remain in use and are permanently improved. Catalytic processes play an important role on silicon surface, and understanding their mechanisms can help find novel applications and obtain new results. It has been noted that indispensable components of various equipment and process designs are recycling steps and combined processes including active distillation. They provide for the most complete utilization of raw trichlorosilane, increase the process yield and cut down silicon cost.